A combination study design to examine mycophenolate mofetil (MMF) and PTLD in renal transplant patients - Maradit Kremers, Hilal; Funch, Donnie P.; Robson, Richard A.; Nalesnik, Michael A.; Ebrahim, Shah; Cecka, Michael J.; Opelz, Gerhard; Dreyer, Nancy A.; Walker, Alexander M. (Pharmacoepidemiology and drug safety, 2000)
Renal transplant recipients who are chronically immunosuppressed by drugs are at a higher risk of developing malignancies. Commonly observed malignancies are several forms of posttransplant lymphoproliferative disorders (PTLD), skin, lip and gynaecological cancers. The risk is associated with many risk factors including the extent of immunosuppression. Mycophenolate mofetil (MMF) is an immunosuppressant, indicated for the prophylaxis of organ rejection in patients receiving allogenic renal and heart transplants. During the European approval of MMF for renal transplantation, the question was raised as to whether the use of MMF was associated with an increased risk of PTLD in comparison with alternate immunosuppressive regimens. In response, F. Hoffman-La Roche Ltd set up a prospective observational cohort study with a companion case-control study. This paper describes the objectives and the methods of these studies along with the rationale of the methodology.